Socio-Economic Profile of Lac Growers in Bastar District of Chhattisgarh State - Dwivedi, Rohit; Shrivastava, K. K.; Pal, Govind (Indian Forester, 2016)
The study was conducted in the year 2012-2013 in Bastar district of Chhattisgarh state. The analysis of data showed that majority of the respondents (68.75%) were involved in lac production + agriculture + labour work. The annual income of lac growers was found that majority (60.00%) have belonged to 20,000 to 40,000 per year. The land holding of lac growers was observed that 51.88 per cent had marginal size of land holding. The credit facilities was found that 88.75 per cent of the respondents had taken credit from forest department, followed by 5.00 per cent of the respondents had taken credit from friends, whereas 3.13 per cent of the respondents had taken credit from neighbours and 3.12 per cent respondents have taken credit from relatives respectively. The result of the study will be helpful in preparation of plans for improving the socio-economic status of lac growers of Bastar district of Chhattisgarh state.